2021
DOI: 10.1186/s12889-021-11527-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of suicide and suicide attempt in northwest of Iran: incidence, predictors, and socioeconomic status and the role of sociocultural status

Abstract: Background A detailed community-level understanding of socioeconomic status (SES) and sociocultural status (SCS) of suicides and suicide attempters (SAs) in a prospective design could have significant implications for policymakers at the local prevention and treatment levels. The effect of SCS and SES on SAs is poorly understood and investigated in Iran. The present study aimed to investigate the incidence, trend, and role of SES and SCS on suicide and SAs. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…These findings highlight the need to consider a wide range of contextual and sociocultural factors on suicide prevention strategies suggested in the community-based studies, at least in Iran [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the need to consider a wide range of contextual and sociocultural factors on suicide prevention strategies suggested in the community-based studies, at least in Iran [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the prevalence of MDD was estimated at 4.1% (3.1-5.1), in a systematic review and meta-analysis [42]. An increase in the prevalence of depressive symptoms can elevate the probability of suicidal behaviors and suicide re-attempt [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a major predictor of suicide. [ 24 ] Awareness of predictors for suicide in depression is imperative for health care systems. [ 25 ] Previous evidence indicated that antidepressants have a positive effect on suicide prevention.…”
Section: Discussionmentioning
confidence: 99%